Study on the selection of sections applicable to truck platooning in the expressway network - Jeong, Harim; Park, Sangmin; Park, Sungho; Cho, Hyonbae; Yun, Ilsoo (Sustainability (Switzerland), 2020)
Several research studies are being actively conducted on truck platooning, in which several trucks are organized in one fleet. The main advantages of truck platooning are increased traffic efficiency, improved fuel consumption and driver performance, and enhanced safety. However, these effects may depend on the actual conditions of road geometry and traffic situation. Therefore, this study analyzed the sustainability of truck platooning on an expressway network in terms of road geometry and traffic situation. To select elements affecting truck platooning on an expressway network, an expert survey was conducted. In addition, the weight of each element selected in the survey was determined through an analytic hierarchy process. In this study, the geometric conformity and traffic environment indices for truck platooning were calculated based on the data collected by the congestion zone (Conzone) and the weights. Moreover, the calculated indices were clustered into three different categories through cluster analysis. Based on the cluster analysis result, each Conzone was classified into three types: Type 1, which is suitable for both traffic environment and geometric conformity to operate platooning; Type 2, which has geometrical conditions but requires improvement of traffic environment; and Type 3, which requires geometrical improvement. Finally, the Type 1 Conzones were expanded to expressway sections to consider the network connectivity and truck platoon operability. The obtained results revealed that 14 sections of 9 expressway lines are most applicable for truck platooning.
Keywords: Analytic hierarchy process; Connectivity; Expressway; Operability; Truck platooning